1995
DOI: 10.1159/000246528
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Melanoma Monoclonal Antibody 225.28S Immunoscintigraphy in Metastatic Melanoma

Abstract: Background: Accurate staging and early detection of metastases are crucial to melanoma management. It would thus be of great value to have a widely available, cost-effective method that allows to examine the whole body and is more specific than current imaging modalities. Objective: The purpose of the study was to assess the value of immunoscintigraphy with 99mTc-radiolabeled F(ab’)2 fragments of the 225.28S monoclonal antibody in the staging of melanoma. Methods: 29 patients with known or suspected metastases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous studies also showed that the anti-CSPG4 225.28 antibody with high affinity (1 × 10 −9 ) for CSPG4 49 , binds to a unique epitope on CSPG4 compared to other clones, and not to ubiquitously expressed carbohydrates 45,[50][51][52] . Furthermore, clone 225.28 has been safely introduced to melanoma patients, suggesting a low risk of off-target-related toxicities 53 for a 225.28-based treatment for melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that the anti-CSPG4 225.28 antibody with high affinity (1 × 10 −9 ) for CSPG4 49 , binds to a unique epitope on CSPG4 compared to other clones, and not to ubiquitously expressed carbohydrates 45,[50][51][52] . Furthermore, clone 225.28 has been safely introduced to melanoma patients, suggesting a low risk of off-target-related toxicities 53 for a 225.28-based treatment for melanoma.…”
Section: Discussionmentioning
confidence: 99%